Quality of life in sarcopenia and frailty. - Rizzoli, R; Reginster, J; Arnal, J; Bautmans, I; Beaudart, C; Bischoff-Ferrari, H; Biver, E; Boonen, S; Brandi, M; Chines, A; Cooper, C; Epstein, S; et al. (2013)
The reduced muscle mass and impaired muscle performance that define sarcopenia in older individuals are associated with increased risk of physical limitation and a variety of chronic diseases. They may also contribute to clinical frailty. A gradual erosion of quality of life (QoL) has been evidenced in these individuals, although much of this research has been done using generic QoL instruments, particularly the SF-36, which may not be ideal in older populations with significant comorbidities. This review and report of an expert meeting presents the current definitions of these geriatric syndromes (sarcopenia and frailty). It then briefly summarizes QoL concepts and specificities in older populations and examines the relevant domains of QoL and what is known concerning QoL decline with these conditions. It calls for a clearer definition of the construct of disability, argues that a disease-specific QoL instrument for sarcopenia/frailty would be an asset for future research, and discusses whether there are available and validated components that could be used to this end and whether the psychometric properties of these instruments are sufficiently tested. It calls also for an approach using utility weighting to provide some cost estimates and suggests that a time trade-off study could be appropriate.